Determinan NonPerformingLoan Bank yang terdaftar di Bursa Efek Indonesia Sebelum dan Selama Pandemi Covid-19 - Deandra Afifah Zerlinda Maidin; Marcellia Susan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to analyze how the influence between Non-Performing Loans and Bank Size, Operating Income Operational Costs (BOPO), Basic Loan Interest Rates (SBDK), and Inflation along with the differences between the five variables in the years before the pandemic, namely 2018 and 2019, and during the pandemic, namely 2020 to 2021. Research Methods using a purposive sampling technique, 37 conventional banks listed on the IDX were obtained for research. Multiple linear regression, paired sample t-test, and Wilcoxon Rank Spearman test are data analysis techniques used. The findings show that all variables simultaneously affect non-performing loans. Variables of Operating Costs, Operating Income and Inflation partially have a positive effect on Non-Performing Loans, but the variables of Bank Size and Basic Loan Interest Rates have no effect on Non-Performing Loans. These various tests show variations between all variables before and during the Covid-19 Pandemic.